The Influence of Marketing Mix on Used Car Purchasing Decision at Jaya Mobil Jakarta - Rafi Alfiando Zaki; Ida Anggriani; Muhammad Rahman Febliansa (Indonesian Journal Publisher, 2025)
This study aims to analyse the effect of marketing mix on used car purchasing decisions at Jaya Mobil Jakarta. The research method used is quantitative with a survey approach through questionnaires distributed to 115 respondents. The data analysis method in this study uses multiple linear regression, validity and reliability tests, hypothesis testing using the F test and t test, and the coefficient of determination. Based on the results of research, overall model testing (simultaneously) that all independent variables have a significant influence on purchasing decisions for used cars at Jaya Mobil Jakarta. Partial testing for product influence has no significant effect on purchasing decisions for used cars at Jaya Mobil Jakarta as well as for partial testing of the effect of place has no significant effect on purchasing decisions for used cars at Jaya Mobil Jakarta. Partial testing for price has a significant effect on purchasing decisions for used cars at Jaya Mobil Jakarta as well as partial testing for promotions has a significant effect on purchasing decisions for used cars at Jaya Mobil Jakarta. Among all the variables studied, the promotion variable has the most dominant influence, as indicated by the standardised beta coefficient of 0.573 and the highest t-count value of 6,881. This research is still limited to the four main elements of the marketing mix, namely: product, price, place (distribution), and promotion that influence purchasing decisions. The marketing mix through integrated elements of product, price, place, and promotion must be maintained and improved because together they have a significant influence on purchasing decisions for used cars at Jaya Mobil Jakarta. For future research, it is recommended to explore other variables that might influence used car purchasing decisions, such as brand image, customer service, after-sales service, or consumer psychological factors